Anemia in premature babies. Pathogenesis, diagnosis, treatment and prevention - E. S. Sakharova; E. S. Keshishian; G. A. Alyamovskaya (Медицинский совет, 2015)
The article is devoted to the diagnosis and treatment of anemia in premature babies in the first 3 years of life. The authors tell about the pathogenetic profile and characteristic clinical manifestations of early and late anemia in premature babies. Results of follow-up of 860 children who were born prematurely including those weighing less than 1,500 g are demonstrated. Based on the results, actions to prevent iron deficiency through targeted follow-up of premature babies as an obligatory phase of nursing are suggested.